Feldenkrais Exercise Mempangaruhi Peningkatan Aktivitas Fungsional Lebih Efektif daripada William Flexion Exercise terhadap Orang dengan Low Back Pain Miogenik - Yuda Saputra; Ahmad Syakib (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
Background : Low Back Pain Miogenik is a lower back pain caused by muscle tension with avery high frequency of cases in workers. This research is done to identify the difference of influence between the approach of William Flexion Exercise and Feldenkrais exercise to functional activity inpatient low back pain miogenik because of the many cases that happened.. Methods : The type of research used is experimental research, research design used is a quasi experiment that compares between two different things. The targets of this study were factory workers with a sampel of 34 people divided into two groups. Result: Based on the result ofhypothesis paired t-test result p-value 0.000 shows both treatment there is significant improvement to functional activity. While on thetest Independentt-test results seen from the mean feldenkrais exercise 8.13 and william flexion exercise 3.25 concluded feldenkrais exercise more up than william flexion exercise.